Hard carbon and its manufacturing method, secondary battery and power consumption device containing the same
Patent Information
- Application Number
- JP2023531033
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-12-31
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-12-31
Smart Images

Figure 0007625083000003 
Figure 0007625083000004 
Figure 0007625083000005
Abstract
Description
[Technical field]
[0001] The present application belongs to the field of battery technology, and in particular to hard carbon and a method for producing the same, as well as a secondary battery and a power consuming device containing the same. [Background technology]
[0002] In recent years, secondary batteries have been widely applied in energy storage power systems such as hydroelectric, thermal, wind and solar power plants, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. With the application and popularity of secondary batteries, their energy density, service life and rate characteristics have attracted more and more attention. Graphite is the most common negative electrode active material in secondary batteries, but its theoretical capacity is only 372 mAh / g, leaving very limited room for improving energy density, and graphite has a small interlayer distance, which limits the improvement of rate characteristics. Hard carbon, as a new negative electrode active material, can realize rapid insertion and desorption of active ions during the charge and discharge process of secondary batteries, and has great potential for development. However, hard carbon has low capacity and initial Coulombic efficiency, which limits the improvement of the energy density, service life and rate characteristics of secondary batteries. Summary of the Invention
[0003] An object of the present application is to provide a hard carbon intended to simultaneously improve the capacity and initial coulombic efficiency of the hard carbon, a method for producing the same, and a secondary battery and power consuming device containing the same.
[0004] A first aspect of the present application provides a hard carbon having a CO2 generation amount of 1.0 mmoL / g or less and a CO generation amount of 2.0 mmoL / g or less, as detected by temperature programmed desorption mass spectrometry (TPD-MS) when the temperature is raised from 50°C to 1,050°C.
[0005] Compared with currently commercialized hard carbons, the hard carbon of the present application has both high capacity and initial coulombic efficiency. Although the mechanism is not yet clear, the inventors of the present application speculate that one possible reason is that the main source of CO2 and CO detected by TPD-MS of hard carbon materials is oxygen-containing functional groups (e.g., phenol groups, ether groups, quinone groups, carbonyl groups, acid anhydrides, ester groups, hydroxyl groups, carboxyl groups, etc.) in the hard carbon structure. The present application controls the content of CO2 and CO generated during the TPD-MS test (corresponding to controlling the content of oxygen-containing functional groups in the hard carbon structure), thereby reducing the probability of oxygen-containing functional groups bonding with active ions and reducing the irreversible consumption of active ions, thereby allowing the hard carbon of the present application to achieve both high capacity and initial coulombic efficiency. At the same time, by controlling the content of oxygen-containing functional groups in the hard carbon structure within a certain range, it is ensured that the structure of the hard carbon material has a suitable amount of defects, and the defects can serve as conductive channels for active ions inside the hard carbon, reducing the proportion of the regions inside the hard carbon that cannot be inserted for active ions, improving the utilization rate of the active ion reaction sites in the hard carbon structure, and favoring the smooth insertion of active ions into the main structure of the hard carbon material, thereby further improving the capacity and initial Coulombic efficiency of the hard carbon.
[0006] In any embodiment of the present application, the amount of CO2 generated detected by temperature programmed desorption mass spectrometry (TPD-MS) when the hard carbon is heated from 50° C. to 1050° C. is 0.2 mmoL / g to 1.0 mmoL / g, and preferably 0.4 mmoL / g to 0.8 mmoL / g. At this time, the hard carbon can have a higher capacity and a higher initial coulombic efficiency, as well as a longer service life and better rate characteristics.
[0007] In any embodiment of the present application, the amount of CO generated by the hard carbon detected by temperature programmed desorption mass spectrometry (TPD-MS) is 0.5 mmoL / g to 2.0 mmoL / g, preferably 0.8 mmoL / g to 1.4 mmoL / g, when the temperature of the hard carbon is increased from 50° C. to 1050° C. In this case, the hard carbon can have a higher capacity and a higher initial coulombic efficiency, as well as a longer service life and better rate characteristics.
[0008] In any embodiment of the present application, the amount of H2 generated by the hard carbon detected by temperature programmed desorption mass spectrometry (TPD-MS) when the temperature of the hard carbon is raised from 50° C. to 1050° C. is 1.0 mmoL / g or less, and preferably 0.5 mmoL / g to 1.0 mmoL / g. H2 is mainly derived from the cleavage of C-H bonds in the hard carbon structure, and since the number of C-H bonds in the hard carbon structure of the present application is small, the active ions stored in the hard carbon structure are easily desorbed, and the voltage hysteresis phenomenon can be significantly suppressed, and therefore the hard carbon can have a higher capacity and a higher initial coulombic efficiency, as well as a longer service life and better rate characteristics.
[0009] In any embodiment of the present application, the mass percentage of the C element in the hard carbon is 95% to 98% with respect to the total mass of the hard carbon.
[0010] In any embodiment of the present application, the mass percentage of the O element in the hard carbon is 5% or less with respect to the total mass of the hard carbon.
[0011] In any embodiment of the present application, the mass percentage of H element in the hard carbon is 0.4% or less with respect to the total mass of the hard carbon. The content of H element in the hard carbon of the present application is small, therefore, the number of C-H bonds in the hard carbon structure is small, and active ions are easily desorbed, so that the hard carbon of the present application can achieve both high capacity and initial coulombic efficiency.
[0012] In any embodiment of the present application, the mass percentage of the N element in the hard carbon is 0.4% or less with respect to the total mass of the hard carbon.
[0013] In any embodiment of the present application, the sum of mass percentages of C, O, H, and N elements of the hard carbon is 99.0% to 99.8% with respect to the total mass of the hard carbon.
[0014] The hard carbon of the present invention has a low content of heteroatoms and therefore has low irreversible consumption of heteroatoms to active ions, which allows the hard carbon of the present invention to achieve both high capacity and initial coulombic efficiency.
[0015] In any embodiment of the present application, in the Raman spectrum of the hard carbon, I d / I g is 1.2 to 1.3, and I d is 1350±50cm -1 represents the d-band peak intensity in the Raman shift range of I g is 1580±50cm -1 The g-band peak intensity in the Raman shift range of I d / I g is 1.2 to 1.3, and at this time, the degree of order of the hard carbon structure is appropriate, so that the hard carbon has both higher capacity and higher initial coulombic efficiency, and further has longer service life and better rate characteristics.
[0016] In any embodiment of the present application, in the X-ray diffraction spectrum of the hard carbon, the 2θ value corresponding to the 002 peak is between 22° and 24°.
[0017] In any embodiment of the present application, the hard carbon has a volume particle size Dv50 of 2 μm to 15 μm, and preferably 4 μm to 8 μm.
[0018] In any embodiment of the present application, the hard carbon has a volume particle size Dv90 of 5 μm to 25 μm, and preferably 8 μm to 15 μm.
[0019] In any embodiment of the present application, the hard carbon has a volume particle diameter Dv50 of 4 μm to 8 μm and a volume particle diameter Dv90 of 8 μm to 15 μm.
[0020] When the volume particle size Dv50 and / or Dv90 of the hard carbon is within an appropriate range, it is advantageous to improve the transport properties of active ions and electrons, thereby further improving the rate characteristics of the hard carbon.
[0021] In any embodiment of the present application, the specific surface area of the hard carbon is 5 m 2 / g or less, preferably 0.5m 2 / g~5m 2 / g. When the specific surface area of the hard carbon is within a suitable range, the hard carbon can have both higher capacity and higher initial coulombic efficiency, and furthermore, has a longer service life and better rate characteristics. In addition, when the specific surface area of the hard carbon is within a suitable range, a stronger bonding force can be formed between the hard carbon and the adhesive, thereby improving the cohesive force and adhesive force of the negative electrode sheet, reducing the volume expansion of the negative electrode sheet during the cycle process, and the secondary battery has better cycle characteristics.
[0022] In any embodiment of the present application, the hard carbon has a green density of 0.96 g / cm3 at an applied force of 50,000 N. 3 ~1.05g / cm 3 When the green density of the hard carbon is within an appropriate range, the green density of the negative electrode sheet can be increased, thereby improving the energy density of the secondary battery.
[0023] In any embodiment of the present application, the tap density of the hard carbon is 0.80 g / cm 3 ~0.95g / cm 3When the tap density of the hard carbon is within an appropriate range, the green density of the negative electrode sheet can be increased, thereby improving the energy density of the secondary battery.
[0024] A second aspect of the present application provides a method for producing hard carbon, the method including: step S10 of providing a carbon source; step S20 of heat-treating the carbon source in an inert atmosphere at a first temperature T1 for t1 hour to obtain a first intermediate product; step S30 of heat-treating the obtained first intermediate product in an oxygen-containing atmosphere having an oxygen volume fraction of 25% or more for t2 hour at a second temperature T2 to obtain a second intermediate product; and step S40 of carbonizing the obtained second intermediate product in an inert atmosphere at a third temperature T3 for t3 hour to obtain hard carbon, wherein the amount of CO2 generated is 1.0 mmoL / g or less and the amount of CO generated is 2.0 mmoL / g or less as detected by temperature programmed desorption mass spectrometry TPD-MS when the hard carbon is heated from 50°C to 1,050°C.
[0025] The inventors have discovered that by simultaneously carrying out a low-temperature heat treatment process in an inert atmosphere, a secondary low-temperature heat treatment process in an oxygen-containing atmosphere, and a high-temperature carbonization process in an inert atmosphere on the carbon source, the resulting hard carbon can have both high capacity and high initial coulombic efficiency. Moreover, compared with conventional commercialized hard carbons, the capacity and initial coulombic efficiency of the hard carbons obtained by the manufacturing method of the present application are both significantly improved.
[0026] The method for producing hard carbon provided by the present application is simple and suitable for commercial production. The method for producing hard carbon provided by the present application does not require the addition of conductive agents or other auxiliary agents, and the hard carbon obtained by the method for producing hard carbon provided by the present application has a lower heteroatom content and can reduce the irreversible consumption of heteroatoms to active ions.
[0027] In any embodiment of the present application, T <T3、T2<T3である。
[0028] In any embodiment of the present application, T1≦T2, preferably T1 <T2である。
[0029] In any embodiment of the present application, T1≦300° C. Preferably, T1 is 180° C. to 300° C. When T1 is within a suitable range, the framework structure of the carbon source can be better stabilized, and a more stable framework structure can be provided for the subsequent pore formation process by high-temperature carbonization, the formation of highly active structural defects can be reduced, and the number of H- and oxygen-containing functional groups in the formed graphite microcrystal structure can be reduced, and the utilization rate of the graphite microcrystal sheet layer as an active ion reaction site can be improved.
[0030] In any embodiment of the present application, T2<400°C. Preferably, T2 is 270°C-380°C. When T2 is within a suitable range, an appropriate amount of oxygen-containing functional groups can be introduced into a stable framework, and these oxygen-containing functional groups are mainly connected to adjacent graphite microcrystal sheet layer precursors by covalent bond, and can maintain a suitable interlayer distance between the graphite microcrystal sheet layers formed during the subsequent high-temperature carbonization treatment, facilitating the reversible desorption and insertion of active ions, while not excessively inhibiting the merging and modification of the graphite microcrystal sheet layers, thereby maximally removing the highly active structural defect sites in the hard carbon, and keeping the generation of CO2, CO and H2 at a low level, ensuring that the hard carbon has both high capacity and high initial Coulombic efficiency.
[0031] In any embodiment of the present application, T3 is 1000° C. to 1600° C. Preferably, T3 is 1000° C. to 1400° C. When T3 is within an appropriate range, the interlayer distance of the graphite crystallites can be increased, the degree of order of the obtained hard carbon can be improved, and the hard carbon can have both high capacity and high initial coulombic efficiency.
[0032] In any embodiment of the present application, t1 is 4 h to 60 h.
[0033] In any embodiment of the present application, t2 is 1h to 12h.
[0034] In any embodiment of the present application, t3 is 1h to 12h.
[0035] In any embodiment of the present application, the volume fraction of oxygen in the oxygen-containing atmosphere is 25% to 100%. Preferably, the volume fraction of oxygen in the oxygen-containing atmosphere is 30% to 80%.
[0036] In any embodiment of the present application, the inert atmosphere is selected from one or more of a nitrogen gas atmosphere and an argon gas atmosphere.
[0037] In any embodiment of the present application, after step S20 and before step S30, the manufacturing method further includes step S21 of crushing the obtained first intermediate product to ensure that the first intermediate product can be sufficiently contacted with oxygen during subsequent processing.
[0038] In any embodiment of the present application, after step S30 and before step S40, the manufacturing method further includes step S31 of crushing the second intermediate product obtained in step S30. Preferably, the volume particle size of the second intermediate product after crushing satisfies the requirement that Dv50 is 2 to 15 μm and / or Dv90 is 5 μm to 25 μm.
[0039] In any embodiment of the present application, the carbon source comprises one or more of a polymer, a resin, and a biomass material.
[0040] In any embodiment of the present application, the polymer comprises one or more of polyaniline, polypyrrole.
[0041] In any embodiment of the present application, the resin comprises one or more of a phenolic resin, an epoxy resin.
[0042] In any embodiment of the present application, the biomass material comprises one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, lignin, and preferably the starch comprises one or more of cereal starch, potato starch, and legume starch.
[0043] A third aspect of the present application provides a secondary battery including a negative electrode sheet comprising the hard carbon according to the first aspect of the present application or the hard carbon produced by the method according to the second aspect of the present application.
[0044] A fourth aspect of the present application provides a power consumption device including a secondary battery according to the third aspect of the present application.
[0045] The power consuming device of the present application includes the secondary battery provided by the present application, and therefore has at least the same advantages as said secondary battery. [Brief description of the drawings]
[0046] In order to more clearly describe the technical solutions in the embodiments of the present application, the following briefly describes the drawings required in the embodiments of the present application. It should be understood that the drawings shown below are only some embodiments of the present application, and those skilled in the art can further obtain other drawings based on the drawings without creative efforts.
[0047] [Figure 1] FIG. 1 is a schematic diagram of a secondary battery according to an embodiment of the present application. [Diagram 2] 2 is an exploded schematic view of the secondary battery shown in FIG. 1 according to the embodiment. [Diagram 3] FIG. 1 is a schematic diagram of an embodiment of a battery module of the present application. [Figure 4] FIG. 1 is a schematic diagram of an embodiment of a battery pack of the present application. [Diagram 5] 5 is an exploded schematic view of the battery pack shown in FIG. 4 according to the embodiment. [Figure 6] 1 is a schematic diagram of an embodiment of a power consuming device including a secondary battery of the present application as a power source. [Figure 7]1 is a scanning electron microscope (SEM) photograph of the hard carbon produced in Example 1. [Figure 8] FIG. 1 shows detection diagrams of molecular weights (m / z) 2, 28, and 44 measured by TPD-MS analysis of the hard carbon produced in Example 2, in which curve I shows molecular weight (m / z) 44, curve II shows molecular weight (m / z) 28, and curve III shows molecular weight (m / z) 2. [Figure 9] FIG. 1 shows detection diagrams of molecular weights (m / z) 2, 28, and 44 measured by TPD-MS analysis of the hard carbon produced in Comparative Example 1, in which curve I shows molecular weight (m / z) 44, curve II shows molecular weight (m / z) 28, and curve III shows molecular weight (m / z) 2.
[0048] In the drawings, the drawings are not drawn to scale. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0049] Hereinafter, the embodiments specifically disclosing the hard carbon of the present application, its manufacturing method, and the secondary battery and power consumption device containing the same will be described in detail with reference to the drawings as appropriate. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and overlapping description of substantially the same structure may be omitted. This is to prevent the following description from becoming unnecessarily redundant and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.
[0050] The "ranges" disclosed herein are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner may or may not include the endpoints and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are recited for a particular parameter, it is understood that the ranges of 60-110 and 80-120 are also contemplated. Also, if minimum range values 1 and 2 are recited, and maximum range values 3, 4, and 5 are recited, the ranges of 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all contemplated. In this application, unless otherwise stated, the numerical range "a-b" means a shorthand representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are fully recited herein, and "0-5" is merely a shorthand for combinations of these numerical values. Additionally, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0051] All embodiments and optional embodiments of the present application, unless otherwise specified, can be combined with each other to form new technical solutions, and such technical solutions should be considered as included in the disclosure of the present application.
[0052] All technical features and optional technical features of the present application, unless otherwise specified, can be combined with each other to form new technical solutions, and such technical solutions should be considered as included in the disclosure of the present application.
[0053] All steps in this application can be performed in sequence or randomly, and are preferably performed in sequence, unless otherwise stated. For example, when the method includes steps (a) and (b), it indicates that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, when the method described may further include step (c), it indicates that step (c) may be added to the method in any order, such as the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0054] The terms "comprise" and "comprises" referred to in this application refer to both open and closed formats unless otherwise specified. For example, the terms "comprise" and "comprises" can indicate that other components not listed may also be included or may include, or that only the listed components may be included or may include.
[0055] In this application, unless otherwise stated, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied by either A being true (or present) and B being false (or absent), or A being false (or absent) and B being true (or present), or both A and B being true (or present).
[0056] In this application, unless otherwise specified, the term "active ion" means an ion that can be inserted and removed back and forth between the positive electrode and the negative electrode of a secondary battery, and includes, but is not limited to, lithium ions, sodium ions, and the like.
[0057] A secondary battery, also called a rechargeable battery or storage battery, is a battery that can continue to be used by activating the active material by charging after the battery is discharged. Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, a separator, and an electrolyte. During the charging and discharging process of the battery, active ions are inserted and removed by going back and forth between the positive electrode sheet and the negative electrode sheet. The separator is installed between the positive electrode sheet and the negative electrode sheet, and mainly serves to prevent short circuit between the positive and negative electrodes, while allowing the active ions to pass through. The electrolyte serves to conduct the active ions between the positive electrode sheet and the negative electrode sheet. At present, secondary batteries are widely used in energy storage power systems such as hydroelectric, thermal, wind, and solar power plants, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace.
[0058] With the application and popularity of secondary batteries, their energy density, service life and rate characteristics have been attracting more and more attention. The characteristics of the negative electrode active material can determine the energy density, service life and safety of the secondary battery to a certain extent. Graphite (which can be divided into natural graphite and synthetic graphite) is the most common negative electrode active material in secondary batteries, but its theoretical capacity is only 372mAh / g, and there is very little room for improving the energy density. In addition, graphite has a small interlayer distance, which limits the improvement of the rate characteristics and cannot meet the actual needs of secondary batteries for high rate characteristics.
[0059] Hard carbon is carbon that is difficult to graphitize, and is difficult to graphitize even at high temperatures of 2500°C or higher. Hard carbon is a carbon material with a complex structure and a graphite microcrystalline structure, where the graphite crystallites are irregularly arranged, the number of graphite microcrystalline layer sheets is small, and the edge faces of the layers may be bridged. The structure of hard carbon also includes amorphous regions, which mainly include pores, defects, sp3 hybridized carbon atoms, carbon chains, some functional groups, etc. Therefore, there may be multiple active ion reaction sites in the structure of hard carbon, such as the surface of graphite microcrystals, between graphite microcrystal layers, the edge faces and pores of graphite microcrystalline layer sheets, etc.
[0060] Compared with graphite, the spacing of hard carbon layers is larger and the pore structure is more abundant, which is therefore favorable for the rapid insertion and desorption of active ions, so that the secondary battery can have excellent low-temperature characteristics, output characteristics and safety, and hard carbon has unique advantages, especially in the field of power batteries. However, most of the hard carbons currently on the market belong to low-capacity common hard carbons, and have low capacity and initial coulombic efficiency, for example, the capacity is generally between 200mAh / g and 280mAh / g, and the initial coulombic efficiency is generally less than 80%, which is quite limited in practical applications.
[0061] Therefore, how to simultaneously improve the capacity and initial coulombic efficiency of hard carbon remains a technical problem that needs to be urgently solved. Hard Carbon
[0062] In view of this, a first aspect of an embodiment of the present application provides a hard carbon that achieves both high capacity and initial coulombic efficiency, and enables a secondary battery to have high energy density, long service life, and excellent rate characteristics.
[0063] The hard carbon according to the first aspect of the present embodiment has a CO2 generation amount of 1.0 mmoL / g or less and a CO generation amount of 2.0 mmoL / g or less, as detected by thermal programmed desorption mass spectrometry (TPD-MS) when the temperature is increased from 50°C to 1,050°C.
[0064] TPD-MS analysis can be performed under the following conditions: a certain mass of sample is placed in a sample tube, the temperature is raised from 50°C to 1050°C at a rate of 1°C / min to 20°C / min in a flow of argon gas or helium gas, the generated gas is continuously quantitatively analyzed by a mass spectrometer, and the substance with molecular weight (m / z) 2 in the detected released gas is regarded as H2, the substance with molecular weight (m / z) 28 as CO, and the substance with molecular weight (m / z) 44 as CO2. After the test is completed, the amount of each gas generated is obtained by time integration of the MS curve obtained by the mass spectrometer, and the obtained gas generation amount is divided by the sample mass, i.e., the amount of gas generated from hard carbon per unit mass in this application.
[0065] An exemplary test method includes the steps of calibrating a mass spectrometer using H2 (molecular weight (m / z) 2), CO (molecular weight (m / z) 28), and CO2 (molecular weight (m / z) 44), placing 100 mg of a sample in a sample tube, introducing argon gas at a flow rate of 10 ml / min to 50 ml / min, purging and gas replacement for 30 minutes, starting the heating device while maintaining the flow of argon gas, and raising the temperature from 50°C to 1050°C at a heating rate of 10°C / min, and continuously quantitatively analyzing the gas generated during the heating process using the mass spectrometer.
[0066] Compared with currently commercialized hard carbons, the hard carbon of the present application has both high capacity and initial coulombic efficiency. Although the mechanism is not yet clear, the inventors of the present application speculate that one possible reason is that the main source of CO2 and CO detected by TPD-MS of hard carbon materials is oxygen-containing functional groups (e.g., phenol groups, ether groups, quinone groups, carbonyl groups, acid anhydrides, ester groups, hydroxyl groups, carboxyl groups, etc.) in the hard carbon structure. The present application controls the content of CO2 and CO generated during the TPD-MS test (corresponding to controlling the content of oxygen-containing functional groups in the hard carbon structure), thereby reducing the probability of oxygen-containing functional groups bonding with active ions and reducing the irreversible consumption of active ions, thereby allowing the hard carbon of the present application to achieve both high capacity and initial coulombic efficiency. At the same time, by controlling the content of oxygen-containing functional groups in the hard carbon structure within a certain range, it is ensured that the structure of the hard carbon material has a suitable amount of defects, and the defects can serve as conductive channels for active ions inside the hard carbon, reducing the proportion of the regions inside the hard carbon that cannot be inserted for active ions, improving the utilization rate of the active ion reaction sites in the hard carbon structure, and favoring the smooth insertion of active ions into the main structure of the hard carbon material, thereby further improving the capacity and initial Coulombic efficiency of the hard carbon.
[0067] In some embodiments, the hard carbon may have a CO2 generation amount detected by temperature programmed desorption mass spectrometry (TPD-MS) of ≦0.9 mmoL / g, ≦0.8 mmoL / g, ≦0.7 mmoL / g, ≦0.6 mmoL / g, ≦0.5 mmoL / g, or ≦0.4 mmoL / g when heated from 50° C. to 1,050° C.
[0068] In some embodiments, the hard carbon may have a CO generation amount detected by temperature programmed desorption mass spectrometry (TPD-MS) when the temperature is increased from 50°C to 1,050°C of ≦1.9 mmoL / g, ≦1.8 mmoL / g, ≦1.7 mmoL / g, ≦1.6 mmoL / g, ≦1.5 mmoL / g, ≦1.4 mmoL / g, ≦1.3 mmoL / g, ≦1.2 mmoL / g, ≦1.1 mmoL / g, ≦1.0 mmoL / g, ≦0.9 mmoL / g, ≦0.8 mmoL / g, ≦0.7 mmoL / g, or 0.6 mmoL / g.
[0069] In some embodiments, the hard carbon can further satisfy the requirement that the amount of CO2 generated is 0.2 mmol / g or more as detected by temperature programmed desorption mass spectrometry (TPD-MS) when the temperature is increased from 50° C. to 1050° C. For example, the amount of CO2 generated is 0.2 mmol / g to 1.0 mmol / g, 0.2 mmol / g to 0.9 mmol / g, 0.2 mmol / g to 0.8 mmol / g, 0.2 mmol / g to 0.7 mmol / g, 0.2 mmol / g to 0.6 mmol / g, 0.2 mmol / g to 0.5 mmol / g, 0.3 mmol / g to 1.0 mmol / g, 0.5 ... .3mmol / g~0.9mmoL / g, 0.3mmol / g~0.8mmoL / g, 0.3mmol / g~0.7mmoL / g, 0.3mmol / g~0.6mmoL / g, 0.3mmol / g~0.5mmoL / g, 0.4mmol / g~1.0mmoL / g, 0.4mmol / g~0.9mmoL / g, 0.4mmol / g~0.8mm oL / g, 0.4mmol / g~0.7mmoL / g, 0.4mmol / g~0.6mmoL / g, 0.4mmol / g~0.5mmoL / g, 0.5mmoL / g~1. 0mmoL / g, 0.5mmoL / g~0.9mmoL / g, 0.5mmoL / g~0.8mmoL / g, 0.5mmoL / g~0.7mmoL / g, 0.5mmoL / g ~0.6mmoL / g, 0.6mmoL / g~1.0mmoL / g, 0.6mmoL / g~0.9mmoL / g, 0.6mmoL / g~0.8mmoL / g, 0.6mmoL / g~0.7mmoL / g, 0.7mmoL / g~1.0mmoL / g, 0.7mmoL / g~0.9mmoL / g, 0.7mmoL / g~0.8mmoL / g. At this time, the hard carbon can have a higher capacity and a higher initial coulombic efficiency, as well as a longer service life and better rate characteristics.
[0070] In some embodiments, the hard carbon can further satisfy the requirement that the amount of CO generated is 0.5 mmol / g or more as detected by temperature programmed desorption mass spectrometry (TPD-MS) when the temperature is increased from 50° C. to 1050° C. For example, the amount of CO generated is 0.5 mmol / g to 2.0 mmol / g, 0.5 mmol / g to 1.8 mmol / g, 0.5 mmol / g to 1.6 mmol / g, 0.5 mmol / g to 1.4 mmol / g, 0.5 mmol / g to 1.2 mmol / g, 0.5 mmol / g to 1.0 mmol / g, 0.5 mmol / g to 0.8 mmol / g, 0.5 mmol / g to 0.6 mmol / g, 0.6 ... / g~2.0mmoL / g, 0.6mmoL / g~1.8mmoL / g, 0.6mmoL / g~1.6mmoL / g, 0.6mmoL / g~1.4mmoL / g, 0.6mmoL / g~1.2mmoL / g, 0.6mmoL / g~1.0mmoL / g, 0.6mmoL / g~0.8mmoL / g, 0.8mmoL / g~2.0mmoL / g, 0.8mmoL / g~1.8mmoL / g, 0.8mmoL / g~2.0mmoL / g, 0.8mmoL / g~1.8mmoL / g, 0.8mmoL / g~2.0mmoL / g, 0.6 ... L / g~1.6mmoL / g, 0.8mmoL / g~1.4mmoL / g, 0.8mmoL / g~1.2mmoL / g, 0.8mmoL / g~1.0mmoL / g, 1.0mmoL / g~2.0mm oL / g, 1.0mmoL / g~1.8mmoL / g, 1.0mmoL / g~1.6mmoL / g, 1.0mmoL / g~1.4mmoL / g, 1.0mmoL / g~1.2mmoL / g, 1.2m moL / g to 2.0mmol / g, 1.2mmol / g to 1.8mmol / g, 1.2mmol / g to 1.6mmol / g, 1.2mmol / g to 1.4mmol / g, 1.4mmol / g to 2.0mmol / g, 1.4mmol / g to 1.8mmol / g, 1.4mmol / g to 1.6mmol / g, 1.6mmol / g to 2.0mmol / g, 1.6mmol / g to 1.8mmol / g. At this time, the hard carbon can have a higher capacity and a higher initial coulombic efficiency, as well as a longer service life and better rate characteristics.
[0071] In some embodiments, the amount of H2 generated by the hard carbon detected by temperature programmed desorption mass spectrometry (TPD-MS) when the temperature is increased from 50°C to 1050°C is 1.0mmoL / g or less, preferably 0.5mmoL / g to 1.0mmoL / g, 0.5mmoL / g to 0.9mmoL / g, 0.5mmoL / g to 0.8mmoL / g, or 0.5mmoL / g to 0.7mmoL / g. g, 0.5mmoL / g-0.6mmoL / g, 0.6mmoL / g-1.0mmoL / g, 0.6mmoL / g-0.9mmoL / g, 0.6mmoL / g-0.8mmoL / g, 0.6mmoL / g-0.7mmoL / g, 0.7mmoL / g-1.0mmoL / g, 0.7mmoL / g-0.9mmoL / g, 0.7mmoL / g-0.8mmoL / g. H2 is mainly derived from the cleavage of C-H bonds in the hard carbon structure, and the number of C-H bonds in the hard carbon structure of the present application is small, and the active ions stored in the hard carbon structure are easy to desorb, and the voltage hysteresis phenomenon can be greatly suppressed, and therefore it can have higher capacity and higher initial coulombic efficiency, as well as longer service life and better rate characteristics.
[0072] In some embodiments, the mass percentage of the C element in the hard carbon is 95% to 98% based on the total mass of the hard carbon.
[0073] In some embodiments, the mass percentage of the O element in the hard carbon is 5% or less, based on the total mass of the hard carbon.
[0074] In some embodiments, the mass percentage of H element in the hard carbon is 0.4% or less, based on the total mass of the hard carbon. The content of H element in the hard carbon of the present application is low, therefore, the number of C-H bonds in the hard carbon structure is small, and active ions are easily desorbed, so that the hard carbon of the present application can achieve both high capacity and initial coulombic efficiency.
[0075] In some embodiments, the mass percentage of the N element in the hard carbon is 0.4% or less, based on the total mass of the hard carbon.
[0076] In some embodiments, the sum of the mass percentages of the C, O, H, and N elements of the hard carbon is 99.0% to 99.8% with respect to the total mass of the hard carbon.
[0077] In some embodiments, with respect to the total mass of the hard carbon, the mass percentage of the C element of the hard carbon is 95% to 98%, the mass percentage of the O element of the hard carbon is 5% or less, the mass percentage of the H element of the hard carbon is 0.4% or less, the mass percentage of the N element of the hard carbon is 0.4% or less, and the sum of the mass percentages of the C, O, H, and N elements of the hard carbon is 99.0% to 99.8%.
[0078] The hard carbon of the present invention has a low content of heteroatoms and therefore has low irreversible consumption of heteroatoms to active ions, which allows the hard carbon of the present invention to achieve both high capacity and initial coulombic efficiency.
[0079] In some embodiments, the Raman spectrum of the hard carbon includes I d / I g is 1.2 to 1.3, and I d is 1350±50cm -1 represents the d-band peak intensity in the Raman shift range of I g is 1580±50cm -1 The Raman shift range of the g-band peak intensity is shown in Fig. 1, and the laser wavelength λ is 532 nm.
[0080] The d-band peak is due to lattice defects of carbon atoms, and the g-band peak is due to the in-plane vibration of sp2 carbon atoms. In hard carbon structures, the d-band peak intensity is related to the number of defects in the hard carbon structure, and the g-band peak intensity is related to the number of graphite crystallites in the hard carbon structure, and therefore, I d / I g can characterize the degree of order in hard carbon structures. d / I g The smaller the I, the higher the degree of order in the hard carbon structure and the higher the perfection of the carbon surface, which improves the initial Coulombic efficiency of the hard carbon, but reduces the capacity and rate characteristics. d / I g is 1.2 to 1.3, and at this time, the degree of order of the hard carbon structure is appropriate, so that the hard carbon has both higher capacity and higher initial coulombic efficiency, and further has longer service life and better rate characteristics.
[0081] In some embodiments, in the X-ray diffraction spectrum of the hard carbon, the 2θ value corresponding to the 002 peak is between 22° and 24°.
[0082] In some embodiments, the specific surface area of the hard carbon is 5 m 2 Preferably, the specific surface area of the hard carbon is 0.1 m 2 / g~5m 2 / g, 0.5m 2 / g~5m 2 / g, 1m 2 / g~5m 2 / g, 1.5m 2 / g~5m 2 / g, 2m 2 / g~5m 2 / g, 2.5m 2 / g~5m 2 / g, 3m 2 / g~5m 2 / g, 3.5m 2 / g~5m 2 / g, 4m 2 / g~5m 2 / g, 0.5m 2 / g~4m 2 / g, 1m 2 / g~4m 2 / g, 1.5m 2 / g~4m 2 / g, 2m 2 / g~4m 2 / g, 2.5m 2 / g~4m 2 / g, 3m 2 / g~4m 2 / g, 0.5m 2 / g~3m 2 / g, 1m 2 / g~3m 2 / g, 1.5m 2 / g~3m 2 / g, 2m 2 / g~3m 2 / g. A lower specific surface area is helpful in reducing the surface activity of the hard carbon and reducing the formation of the SEI film, thereby improving the initial Coulombic efficiency of the hard carbon and the secondary battery, and a higher specific surface area is helpful in accelerating the transport of active ions, thereby improving the rate characteristics of the secondary battery. When the specific surface area of the hard carbon is within a suitable range, the hard carbon can have both a higher capacity and a higher initial Coulombic efficiency, and also has a longer service life and better rate characteristics. In addition, when the specific surface area of the hard carbon is within a suitable range, the hard carbon can have a stronger bonding force between the hard carbon and the adhesive, thereby improving the cohesive force and adhesive force of the negative electrode sheet, reducing the volume expansion of the negative electrode sheet during the cycle process, and the secondary battery has better cycle characteristics.
[0083] In some embodiments, the hard carbon has a volume particle size Dv50 of 2 μm to 15 μm, preferably 4 μm to 8 μm.
[0084] In some embodiments, the hard carbon has a volume particle size Dv90 of 5 μm to 25 μm, preferably 8 μm to 15 μm.
[0085] In some embodiments, the hard carbon has a volume particle size Dv50 of 4 μm to 8 μm and a volume particle size Dv90 of 8 μm to 15 μm.
[0086] When the volume particle size Dv50 and / or Dv90 of the hard carbon is within an appropriate range, it is advantageous to improve the transport properties of active ions and electrons, thereby further improving the rate characteristics of the hard carbon.
[0087] In some embodiments, the hard carbon has a green density of 0.96 g / cm at a force of 50,000 N. 3 ~1.05g / cm 3 When the green density of the hard carbon is within an appropriate range, the green density of the negative electrode sheet can be increased, thereby improving the energy density of the secondary battery.
[0088] In some embodiments, the hard carbon has a tap density of 0.80 g / cm 3 ~0.95g / cm 3 When the tap density of the hard carbon is within an appropriate range, the green density of the negative electrode sheet can be increased, thereby improving the energy density of the secondary battery.
[0089] In some embodiments, when the hard carbon is heated from 50° C. to 1,050° C., the amount of CO2 generated detected by temperature programmed desorption mass spectrometry (TPD-MS) is 0.2 mmoL / g to 1.0 mmoL / g, the amount of CO generated detected is 0.5 mmoL / g to 2.0 mmoL / g, and the amount of H2 generated detected is 0.5 mmoL / g to 1.0 mmoL / g.
[0090] In some embodiments, when the hard carbon is heated from 50° C. to 1,050° C., the amount of CO2 generated detected by temperature programmed desorption mass spectrometry (TPD-MS) is 0.4 mmoL / g to 0.8 mmoL / g, the amount of CO generated detected is 0.8 mmoL / g to 1.4 mmoL / g or less, and the amount of H2 generated detected is 0.5 mmoL / g to 1.0 mmoL / g.
[0091] In the present application, the TPD-MS analysis can be performed using an Autochem Model II 2920 gas analyzer from Micromeritics Instruments Corporation, USA, and a Hiden HPR-20 R&D mass spectrometer from Hiden Analytical Ltd., UK.
[0092] In the present application, the specific surface area of the hard carbon can be measured using an ASAP 3020 type surface area and pore size analyzer manufactured by Micromeritics Instruments Corporation, USA. GB / T 19587-2017 can be referred to during testing. The specific surface area was measured using a nitrogen adsorption specific surface area analysis test method, and the specific surface area of the hard carbon was calculated using the BET (Brunauer Emmett Teller) method.
[0093] In this application, the volumetric particle size Dv50 and Dv90 of hard carbon have the meanings known in the art, which indicate the particle size when the cumulative volume distribution percentage of the material reaches 50% and 90%, respectively, and can be measured using devices and methods known in the art, for example, see GB / T 19077-2016 Particle Size Distribution Laser Diffraction Method, which can be easily measured using a laser particle size analyzer such as the Mastersizer 2000E type laser particle size analyzer manufactured by Malvern Corporation, UK.
[0094] In this application, the green density of hard carbon has a meaning known in the art and can be measured using devices and methods known in the art. For example, it can be measured by an electronic pressure tester (such as UTM7305 type) with reference to the recommended standard GB / T24533-2009. An exemplary test method is to weigh 1 g of hard carbon powder and measure the density of the powder having a base area of 1.327 cm. 2 The mixture is placed in a mold, pressurized to 5000 kg (equivalent to 50,000 N), and held for 30 seconds before releasing the pressure and holding for 10 seconds. The green density of the hard carbon under a force of 50,000 N is then recorded and calculated.
[0095] In this application, the tap density of hard carbon has a meaning known in the art and can be measured using an apparatus and method known in the art, for example, referring to GB / T 5162-2006, and can be measured using a powder tap density meter (such as Dandong Baite BT-301).
[0096] In the present application, the element content of hard carbon has a meaning known in the art, and can be measured using an apparatus and method known in the art, for example, by X-ray photoelectron spectroscopy (XPS). Manufacturing method of hard carbon
[0097] A second aspect of the present invention provides a method for producing hard carbon, comprising the steps of: providing a carbon source (S10); heat-treating the carbon source in an inert atmosphere at a first temperature (T1) for t1 hours to obtain a first intermediate product (S20); heat-treating the first intermediate product in an oxygen-containing atmosphere having an oxygen volume fraction of 25% or more for t2 hours to obtain a second intermediate product (S30); and carbonizing the second intermediate product in an inert atmosphere at a third temperature (T3) for t3 hours to obtain hard carbon (S40). When the hard carbon is heated from 50°C to 1050°C, the amount of CO2 generated is detected by temperature-programmed desorption mass spectrometry (TPD-MS) of 1.0mmoL / g or less, and the amount of CO generated is detected of 2.0mmoL / g or less.
[0098] The production method according to the second aspect of the embodiment of the present application can produce hard carbon according to any of the examples in the first aspect of the embodiment of the present application.
[0099] In some embodiments, T <T3であり、T2<T3である。
[0100] In some embodiments, T1≦T2. Preferably, T1 <T2である。
[0101] The inventors have discovered that by simultaneously carrying out a low-temperature heat treatment process in an inert atmosphere, a secondary low-temperature heat treatment process in an oxygen-containing atmosphere, and a high-temperature carbonization process in an inert atmosphere on the carbon source, the resulting hard carbon can have both high capacity and high initial coulombic efficiency. Moreover, compared with conventional commercialized hard carbons, the capacity and initial coulombic efficiency of the hard carbons obtained by the manufacturing method of the present application are both significantly improved.
[0102] The method for producing hard carbon provided by the present application is simple and suitable for commercial production.
[0103] The method for producing hard carbon provided by the present application does not require the addition of a conductive agent or other auxiliary agents, and the hard carbon obtained by the method for producing hard carbon provided by the present application has a lower heteroatom content and can reduce the irreversible consumption of heteroatoms to active ions.
[0104] In the method for producing hard carbon of the present application, the carbon source is heat-treated in an inert atmosphere at a low first temperature to better stabilize the framework structure of the carbon source and provide a stable framework structure for the pore formation process by the subsequent high-temperature carbonization. The first intermediate product is heat-treated in an oxygen-containing atmosphere at a low second temperature to introduce an appropriate amount of oxygen-containing functional groups, which are mainly connected to adjacent graphite microcrystalline sheet layer precursors by covalent bonds, and can maintain an appropriate interlayer distance between the graphite microcrystalline sheet layers formed during the subsequent high-temperature carbonization, facilitating the reversible desorption and insertion of active ions, while not excessively inhibiting the merging and modification of the graphite microcrystalline sheet layers. The second intermediate product is high-temperature carbonized in an inert atmosphere at a high third temperature to improve the degree of order of the obtained hard carbon.
[0105] In some embodiments, the volume fraction of oxygen in the oxygen-containing atmosphere is 25%-100%. Also, it is not preferable that the volume fraction of oxygen in the oxygen-containing atmosphere is too high. When the volume fraction of oxygen in the oxygen-containing atmosphere is high, a large amount of the supporting skeleton in the obtained first intermediate product structure will chemically react with oxygen and dissipate in the form of small molecules, such as CO2, CO, etc., and the number of oxygen-containing functional groups introduced into the skeleton material will be small, and in the subsequent high-temperature heat treatment process, the small number of oxygen-containing functional groups will not be able to effectively inhibit the mutual approach of adjacent sheet layers of graphite crystallites, so that some graphite crystallites will not be able to insert active ions due to the small interlayer distance, which may reduce the capacity of hard carbon.
[0106] In some embodiments, the oxygen-containing atmosphere is a mixed atmosphere of oxygen and an inert gas, and preferably has a volume fraction of oxygen of 25% to 80%, 30% to 80%, 40% to 80%, 50% to 80%, 25% to 70%, 30% to 70%, 40% to 70%, 50% to 70%, 25% to 60%, 30% to 60%, 40% to 60%, 25% to 50%, or 30% to 50%.
[0107] The present application does not particularly limit the type of inert atmosphere, and in some embodiments, the inert atmosphere is selected from one or more of a nitrogen gas atmosphere and an argon gas atmosphere.
[0108] In some embodiments, the heating rate in S20 may be 1°C / min to 10°C / min. However, the present application is not limited thereto, and the heating rate can be adjusted according to the actual situation. For example, the heating rate is 1°C / min to 9°C / min, 1°C / min to 8°C / min, 1°C / min to 7°C / min, 1°C / min to 6°C / min, 1°C / min to 5°C / min, 1°C / min to 4°C / min, 1°C / min to 3°C / min, 1°C / min to 2°C / min, 2°C / min to 10°C / min, 3°C / min to 9°C / min, 4°C / min to 8°C / min, or 5°C / min to 7°C / min.
[0109] In some embodiments, the first temperature T1 is 300° C. or less. When the first temperature T1 is high, many molecular chains inside the carbon source are easily cut during the heat treatment, and many structural defects due to atomic deficiencies are introduced into the skeleton structure. The structural defects located on the bottom surface and some end surfaces of the graphite crystallites do not bond with hydrogen, but have high activity, so they react with O2, H2O, etc. in the air at the moment when the hard carbon is produced and taken out of the furnace, and a large amount of oxygen-containing functional groups are introduced into the obtained hard carbon. The end surfaces of the graphite crystallites in the hard carbon mainly introduce functional groups such as carboxyl groups, carbonyl groups, and quinone groups, and the bottom surfaces of the graphite crystallites in the hard carbon mainly introduce functional groups such as hydroxyl groups, ether groups, etc., and the carboxyl group functional groups mainly increase the amount of CO2 generated, and the carbonyl groups, quinone groups, hydroxyl groups, and ether groups mainly increase the amount of CO generated. The oxygen-containing functional groups introduced in this part after the production is completed cannot reversibly release the active ions after combining with the active ions, and the obtained hard carbon has a low initial Coulombic efficiency. In addition, the oxygen-containing functional groups introduced after the completion of production cause the SEI film formed on the hard carbon surface to have a complex chemical composition and a large thickness, which is disadvantageous for desolvation of active ions, and the volume of the obtained hard carbon is also small.
[0110] Moreover, it is not preferable that the first temperature T1 is too low. If the first temperature T1 is low, the degree of crosslinking after the heat treatment of the carbon source is low, the chemical stability of the formed skeleton structure is low, and when the second low-temperature heat treatment is performed in an oxygen-containing atmosphere, a large number of chemical bonds in the skeleton structure are still broken and a large number of structural defects are formed, and the number of H and oxygen-containing functional groups in the graphite microcrystal structure formed during the high-temperature carbonization treatment is still large. Therefore, if the first temperature T1 is low, the generation amounts of CO2, CO and H2 in the TPD-MS analysis of the obtained hard carbon increase to a certain extent, and the capacity and initial coulombic efficiency of the obtained hard carbon decrease to a certain extent.
[0111] In some embodiments, the first temperature T1 may be 180°C to 300°C, 200°C to 300°C, 220°C to 300°C, 240°C to 300°C, 260°C to 300°C, 280°C to 300°C, 180°C to 280°C, 200°C to 280°C, 220°C to 280°C, 240°C to 280°C, 260°C to 280°C, 180°C to 260°C, 200°C to 260°C, 220°C to 260°C, 240°C to 260°C, 180°C to 240°C, 200°C to 240°C, 220°C to 240°C, or 180°C to 220°C. When the first temperature T1 is within a suitable range, the framework structure of the carbon source can be better stabilized, and a more stable framework structure can be provided for the subsequent pore formation process by high-temperature carbonization, the formation of highly active structural defects can be reduced, and the number of H- and oxygen-containing functional groups in the graphite microcrystal structure formed can be reduced, improving the utilization of the graphite microcrystal sheet layer as an active ion reaction site. Therefore, when the first temperature T1 is within a suitable range, the obtained hard carbon can achieve both high capacity and initial coulombic efficiency.
[0112] In some embodiments, the heat treatment time t1 is 4h to 60h. Those skilled in the art can select an appropriate heat treatment time within the above range according to the first temperature used, for example, when the first temperature is high, the heat treatment time can be appropriately shortened. The heat treatment time also varies somewhat depending on the type of carbon source, and those skilled in the art can adjust it according to the actual situation.
[0113] In some embodiments, the heating rate in step S30 may be 1° C. / min to 5° C. / min. However, the present application is not limited thereto, and the heating rate can be adjusted according to the actual situation. For example, the heating rate is 1° C. / min to 4° C. / min, 1° C. / min to 3° C. / min, 1° C. / min to 2° C. / min, 2° C. / min to 5° C. / min, 2° C. / min to 4° C. / min, 2° C. / min to 3° C. / min, 3° C. / min to 5° C. / min, 3° C. / min to 4° C. / min, or 4° C. / min to 5° C. / min.
[0114] In some embodiments, the second temperature T2 is less than 400° C. If the second temperature T2 is too high, a large amount of the supporting framework in the first intermediate product structure obtained in step S20 will react with oxygen and dissipate in the form of small molecules, such as CO2, CO, etc. Thus, many structural defects will be introduced into the obtained hard carbon structure, the number of H and oxygen-containing functional groups in the formed graphite microcrystal structure will be increased, and the generation of CO2, CO, and H2 will increase to a certain extent in the TPD-MS analysis of the hard carbon, and the capacity and initial Coulombic efficiency of the hard carbon will be reduced to a certain extent. Furthermore, it is also undesirable that the second temperature T2 is too low. If the second temperature T2 is low, the number of oxygen-containing functional groups introduced into the framework material will be small, and in the subsequent high-temperature heat treatment process, the small number of oxygen-containing functional groups will not be able to effectively inhibit the mutual approach of adjacent sheet layers of the graphite microcrystals, so that some graphite microcrystals will not be able to insert active ions due to the small interlayer distance. Thus, the capacity of the hard carbon will also be reduced to a certain extent.
[0115] In some embodiments, the second temperature T2 is 200°C to 400°C, 220°C to 400°C, 240°C to 400°C, 260°C to 400°C, 280°C to 400°C, 300°C to 400°C, 320°C to 400°C, 340°C to 400°C, 360°C to 400°C, 200°C to 380°C, 220°C to 380°C, 2 40℃~380℃, 260℃~380℃, 270℃~350℃, 270℃~380℃, 280℃~380℃, 290℃~380℃, 290℃~350℃, 300℃~380℃, 320℃~380℃, 340℃~380℃, 360℃~380℃, 200℃~360℃, 220℃~360℃, 240 ℃~360℃, 260℃~360℃, 280℃~360℃, 300℃~360℃, 320℃~360℃, 200℃~340℃, 220℃~340℃, 240℃~340℃, 260℃~340℃, 280℃~340℃, 300℃~340℃, 200℃~320℃, 220℃~320℃, 240℃~ The temperature may be 320°C, 260°C to 320°C, 280°C to 320°C, 200°C to 300°C, 220°C to 300°C, 240°C to 300°C, 260°C to 300°C, 200°C to 280°C, 220°C to 280°C, 240°C to 280°C, 200°C to 260°C, 220°C to 260°C, or 200°C to 240°C. When the second temperature T2 is within a suitable range, an appropriate amount of oxygen-containing functional groups can be introduced into the stable framework, and these oxygen-containing functional groups are mainly connected to adjacent graphite microcrystal sheet layer precursors by covalent bonds, so that a suitable interlayer distance can be maintained between the graphite microcrystal sheet layers formed during the subsequent high-temperature carbonization treatment, facilitating the reversible desorption and insertion of active ions, while not excessively inhibiting the merging and modification of the graphite microcrystal sheet layers, thereby maximally removing the highly active structural defect sites in the hard carbon, and keeping the generation of CO2, CO and H2 at a low level, ensuring that the hard carbon has both high capacity and high initial Coulombic efficiency.
[0116] In some embodiments, the heat treatment time t2 is from 1 h to 12 h. A person skilled in the art can select an appropriate heat treatment time within the above range according to the second temperature and oxygen concentration adopted. For example, the higher the second temperature or the higher the oxygen concentration, the more appropriately the heat treatment time can be shortened. The heat treatment time also varies somewhat depending on the type of carbon source, and a person skilled in the art can adjust it according to the actual situation.
[0117] In some embodiments, preferably, when T2≤270 °C, T2≥10 h. Further, when 200 °C≤T2≤270 °C, 10 h≤T2≤12 h.
[0118] In some embodiments, preferably, when 270 °C<T2<400 °C, T2≤8 h. Further, when 270 °C<T2<400 °C, 1 h≤T2≤8 h
[0119] In some embodiments, 270 °C≤T2≤380 °C and 1 h≤T2≤4 h. When both meet the requirements within the above range, the capacity of the hard carbon and the initial Coulomb efficiency can be further improved.
[0120] In some embodiments, the heating rate in step S40 is from 1 °C / min to 10 °C / min. However, the present application is not limited thereto, and the heating rate can be adjusted according to the actual situation. For example, the heating rate can be 1 °C / min to 9 °C / min, 1 °C / min to 8 °C / min, 1 °C / min to 7 °C / min, 1 °C / min to 6 °C / min, 1 °C / min to 5 °C / min, 1 °C / min to 4 °C / min, 1 °C / min to 3 °C / min, 1 °C / min to 2 °C / min, 2 °C / min to 10 °C / min, 3 °C / min to 9 °C / min, 4 °C / min to 8 °C / min, 5 °C / min to 7 °C / min.
[0121] In some embodiments, the third temperature T3 is 1000°C to 1600°C. If the third temperature T3 is low, a large amount of highly active structural defects introduced into the second intermediate product structure obtained in step S30 cannot be effectively reduced by the low heat treatment temperature, so that the graphite crystallites contain a large amount of oxygen-containing functional groups that can be decomposed to generate CO2, CO and H2, and the capacity and initial Coulombic efficiency of the obtained hard carbon are reduced to a certain extent. In addition, it is not preferable that the third temperature T3 is too high. If the third temperature T3 is high, the adjacent sheet layers of the graphite crystallites are significantly moved closer to each other, and if the third temperature T3 is high, fine movement of the graphite crystallites is likely to occur, and the supporting effect of the oxygen-containing functional groups located between the adjacent sheet layers of the graphite crystallites introduced in step S30 is insufficient to resist the fine movement of the graphite crystallites, and finally the interlayer distance of some graphite crystallite sheet layers is small, and active ions cannot be inserted, and the capacity of the obtained hard carbon is reduced to a certain extent.
[0122] In some embodiments, the third temperature T3 is 1100°C to 1600°C, 1200°C to 1600°C, 1300°C to 1600°C, 1400°C to 1600°C, 1500°C to 1600°C, 1000°C to 1500°C, 1100°C to 1500°C, 1200°C to 1500°C, 1300°C to 1500°C, 1400°C to 1500°C, 0°C, 1000°C to 1350°C, 1000°C to 1400°C, 1100°C to 1400°C, 1200°C to 1400°C, 1300°C to 1400°C, 1000°C to 1300°C, 1100°C to 1300°C, 1200°C to 1300°C, 1000°C to 1200°C, 1100°C to 1200°C, 1000°C to 1100°C. When the third temperature T3 is within a suitable range, the interlayer distance of the graphite crystallites can be improved, the degree of order of the obtained hard carbon is improved, and the hard carbon has both high capacity and high initial Coulombic efficiency.
[0123] In some embodiments, the heat treatment time t3 is 1h to 12h. Those skilled in the art can select an appropriate heat treatment time within the above range according to the third temperature used, for example, when the third temperature is high, the heat treatment time can be appropriately shortened. The heat treatment time also varies somewhat depending on the type of carbon source, and those skilled in the art can adjust it according to the actual situation.
[0124] In some embodiments, the method for producing the hard carbon may further include a crushing step, which can prevent the hard carbon from agglomerating in large amounts during the production process and help obtain hard carbon that meets the required size requirements.
[0125] In the method for producing hard carbon of the present application, the crushing treatment must be performed before the high-temperature carbonization treatment. This is because if the crushing treatment is performed on the obtained hard carbon after the high-temperature carbonization treatment is completed, many new surfaces will be exposed on the hard carbon, and these new surfaces will be prone to react with O2, H2O, etc. in the air, and a large amount of oxygen-containing functional groups will be introduced into the obtained hard carbon, reducing the capacity and initial coulombic efficiency of the obtained hard carbon. The crushing treatment may be to crush the first intermediate product and / or the second intermediate product.
[0126] In some embodiments, after step S20 and before step S30, the method further includes step S21 of crushing the obtained first intermediate product, for example, crushing to the order of mm, to crush the agglomerated first intermediate product at this time, so as to ensure that the first intermediate product can be sufficiently contacted with oxygen during subsequent processing, although in some embodiments, this step may be omitted.
[0127] In some embodiments, after step S30 and before step S40, the manufacturing method further includes step S31 of crushing the second intermediate product obtained in step S30. For example, in some embodiments, the volume particle size Dv50 of the second intermediate product after crushing is 2 μm to 15 μm, preferably 4 μm to 8 μm. In some embodiments, the volume particle size Dv90 of the second intermediate product after crushing is 5 μm to 25 μm, preferably 8 μm to 15 μm. In some embodiments, the volume particle size Dv50 of the second intermediate product after crushing is 4 μm to 8 μm, and the volume particle size Dv90 is 8 μm to 15 μm.
[0128] The present application does not particularly limit the type of carbon source, and in some embodiments, the carbon source includes one or more of a polymer, a resin, and a biomass material.
[0129] By way of example, the polymer may include one or more of polyaniline, polypyrrole.
[0130] For example, the resin may include one or more of a phenolic resin, an epoxy resin, and preferably, the phenolic resin may include one or more of a phenol-formaldehyde resin, a resorcinol-formaldehyde resin, a hydroquinone-formaldehyde resin, and a phenol-furfural resin.
[0131] By way of example, the biomass material comprises one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, lignin. Preferably, the starch comprises one or more of cereal starch, potato starch, legume starch. Examples of cereal starch include, but are not limited to, one or more of corn starch, rice starch, millet starch, sorghum starch, wheat starch, oat starch, buckwheat starch, rye starch, examples of potato starch include, but are not limited to, one or more of cassava starch, potato starch, sweet potato starch, yam starch, taro starch, examples of legume starch include, but are not limited to, one or more of mung bean starch, broad bean starch, pea starch, cowpea starch.
[0132] Preferably, the carbon source is selected from biomass materials. Furthermore, the carbon source is selected from one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, and lignin. The above biomass materials have a small number of heteroatoms (atoms other than O and H), a high carbon element content, and low cost, which can avoid the influence of heteroatoms on the hard carbon production process. In addition, the above biomass materials can be crosslinked at low temperatures, which is favorable for forming a more stable skeleton structure, thereby obtaining hard carbon with a suitable channel structure.
[0133] In the present application, the biomass material may be commercially available or may be obtained by extraction from plants.
[0134] In some embodiments, the method for producing the hard carbon includes the steps of: providing starch as a carbon source (S10); heat-treating the carbon source in an inert atmosphere at a temperature of 300°C or less for 4h to 60h to obtain a first intermediate product (S20); heat-treating the first intermediate product in an oxygen-containing atmosphere having an oxygen volume fraction of 25% or more for 1h to 12h at a temperature of 400°C or less for 1h to 12h to obtain a second intermediate product (S30); and carbonizing the second intermediate product in an inert atmosphere at a temperature of 1000°C to 1600°C for 1h to 12h to obtain hard carbon (S40). When the hard carbon is heated from 50°C to 1050°C, the amount of CO2 generated is detected by temperature-programmed desorption mass spectrometry (TPD-MS) of 1.0mmoL / g or less, and the amount of CO generated is detected of 2.0mmoL / g or less.
[0135] In some embodiments, the method for producing the hard carbon includes the steps of: providing starch as a carbon source (S10); heat-treating the carbon source in an inert atmosphere at a temperature of 300°C or less for 4 to 60 hours to obtain a first intermediate product (S20); heat-treating the first intermediate product in an oxygen-containing atmosphere having an oxygen volume fraction of 25% or more for 1 to 12 hours at a temperature of 400°C or less to obtain a second intermediate product (S30); and crushing the second intermediate product to a volume particle size Dv50 of 2 μm to 15 μm and / or a volume particle size Dv90 of 5 μm to 25 μm, and carbonizing the second intermediate product in an inert atmosphere at a temperature of 1000°C to 1600°C for 1 to 12 hours to obtain hard carbon (S40). When the hard carbon is heated from 50° C. to 1,050° C., the amount of CO2 generated detected by thermal programmed desorption mass spectrometry (TPD-MS) is 1.0 mmoL / g or less, and the amount of CO generated detected is 2.0 mmoL / g or less. secondary battery
[0136] A third aspect of the present embodiment provides a secondary battery. The type of the secondary battery is not particularly limited, and for example, the secondary battery may be a lithium ion battery, a sodium ion battery, etc., and in particular, the secondary battery is a sodium ion secondary battery. In general, the secondary battery includes a positive electrode sheet, a negative electrode sheet, and an electrolyte. During the charge and discharge process of the secondary battery, active ions are inserted and removed by reciprocating between the positive electrode sheet and the negative electrode sheet, and the electrolyte serves to conduct the active ions between the positive electrode sheet and the negative electrode sheet. [Negative electrode sheet]
[0137] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer provided on at least one surface of the negative electrode current collector and including a negative electrode active material. For example, the negative electrode current collector has two opposing surfaces in its thickness direction, and the negative electrode film layer is provided on either one or both of the two opposing surfaces of the negative electrode current collector.
[0138] In some embodiments, the negative electrode film layer comprises at least one of the hard carbon described in any of the embodiments in the first aspect of the present application, and the hard carbon produced by the method described in any of the embodiments in the second aspect of the present application.
[0139] In some embodiments, the negative electrode film layer may further include other negative electrode active materials other than the hard carbon. In some embodiments, the other negative electrode active materials may include, but are not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based materials may include at least one of silicon elemental, silicon oxide, silicon carbon composite, silicon nitrogen composite, and silicon alloy materials. The tin-based materials may include at least one of tin elemental, tin oxide, and tin alloy materials. The present application is not limited to these materials, and other known materials that can be used as negative electrode active materials for secondary batteries may be used.
[0140] In some embodiments, the negative electrode film layer preferably further comprises a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent, and for example, the negative electrode conductive agent may comprise at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≦5% with respect to the total mass of the negative electrode film layer.
[0141] In some embodiments, the negative electrode film layer preferably further includes a negative electrode binder. The present application does not particularly limit the type of the negative electrode binder, and for example, the negative electrode binder can include at least one of styrene butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder is ≦5% relative to the total mass of the negative electrode film layer.
[0142] In some embodiments, the negative electrode film layer preferably further comprises other additives. For example, the other additives may comprise a thickener, such as sodium carboxymethylcellulose (CMC-Na), a PTC thermistor material, etc. In some embodiments, the mass percentage of the other additives is ≦2% based on the total mass of the negative electrode film layer.
[0143] In some embodiments, the negative electrode current collector can be a metal foil or a composite current collector. The metal foil can be, for example, a copper foil. The composite current collector can include a polymer substrate layer and a metal material layer formed on at least one surface of the polymer substrate layer. For example, the metal material can be selected from at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymer substrate layer can be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0144] The negative electrode film layer is generally formed by applying a negative electrode paste to a negative electrode current collector, drying, and cold pressing. The negative electrode paste is generally formed by dispersing a negative electrode active material, preferably a conductive agent, a binder, and other optional auxiliary agents in a solvent, and stirring the mixture uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.
[0145] The negative electrode sheet does not exclude additional functional layers other than the negative electrode film layer. For example, in some embodiments, the negative electrode sheet described herein further includes a conductive primer layer (e.g., made of a conductive agent and a binder) sandwiched between the negative electrode collector and the negative electrode film layer and provided on the surface of the negative electrode collector. In other embodiments, the negative electrode sheet described herein further includes a protective layer covering the surface of the negative electrode film layer. [Positive electrode sheet]
[0146] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer provided on at least one surface of the positive electrode current collector. For example, the positive electrode current collector has two opposing surfaces in the thickness direction of the positive electrode current collector, and the positive electrode film layer is provided on one or both of the two opposing surfaces of the positive electrode current collector.
[0147] The positive electrode current collector can be a metal foil or a composite current collector. The metal foil can be, for example, an aluminum foil. The composite current collector can include a polymer substrate layer and a metal material layer formed on at least one surface of the polymer substrate layer. For example, the metal material can be selected from one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. For example, the polymer substrate layer can be selected from polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0148] The positive electrode film layer generally includes a positive electrode active material, preferably a binder, and preferably a conductive agent. The positive electrode film layer is generally formed by applying a positive electrode paste to the positive electrode current collector, drying, and cold pressing. The positive electrode paste is generally formed by dispersing the positive electrode active material, preferably a conductive agent, a binder, and other optional components in a solvent and stirring uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP). For example, the binder used in the positive electrode film layer may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin. By way of example, conductive agents used in the positive electrode film layer include one or more of superconducting carbon, conductive graphite, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0149] As the positive electrode active material, a positive electrode active material for secondary batteries known in the art can be used.
[0150] When the secondary battery of the present application is a lithium-ion battery, the positive electrode active material can include one or more of lithium transition metal oxides, lithium-containing phosphates having an olivine structure, and modified compounds thereof. Examples of lithium transition metal oxides can include, but are not limited to, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and one or more of their modified compounds. Examples of lithium-containing phosphates having an olivine structure can include, but are not limited to, lithium iron phosphate, a composite of lithium iron phosphate and carbon, lithium manganese phosphate, a composite of lithium manganese phosphate and carbon, lithium ferromanganese phosphate, a composite of lithium ferromanganese phosphate and carbon, and one or more of their modified compounds. The present application is not limited to these materials, and other known materials that can be used as the positive electrode active material of a lithium-ion battery can be used. These positive electrode active materials may be used alone, or two or more of them may be used in combination.
[0151] In some embodiments, in order to further increase the energy density of the secondary battery, the positive electrode active material used in the lithium-ion battery can include one or more of the lithium transition metal oxides represented by formula (1) and their modified compounds, Li a Ni b Co c M d O e A f (1) In formula 1, 0.8 ≦ a ≦ 1.2, 0.5 ≦ b < 1, 0 < c < 1, 0 < d < 1, 1 ≦ e ≦ 2, 0 ≦ f ≦ 1, M is selected from one or more of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, B, and A is selected from one or more of N, F, S, Cl.
[0152] For example, the positive electrode active materials used in lithium ion batteries are LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co 0.15 Al 0.05 It may include one or more of O2, LiFePO4, and LiMnPO4.
[0153] When the secondary battery of the present application is a sodium ion battery, and particularly when the secondary battery is a sodium ion secondary battery, the positive electrode active material may include one or more of a sodium-containing transition metal oxide, a polyanion material (e.g., phosphate, fluorophosphate, pyrophosphate, sulfate, etc.), and a Prussian blue-based material. The present application is not limited to these materials, and other known materials that can be used as positive electrode active materials for sodium ion batteries may be used. These positive electrode active materials may be used alone or in combination of two or more.
[0154] For example, the positive electrode active materials used in sodium ion batteries are NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2, NaNi 1 / 2 Mn 1 / 2 O2, Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2, NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue-based materials, general formula A a M b (PO4)c O x Y 3-x The material of (A is H + 、Li + 、Na + 、K +、 NH4 + selected from one or more of them, M is a transition metal cation, preferably one or more of V, Ti, Mn, Fe, Co, Ni, Cu, Zn, Y is a halogen anion, preferably one or more of F, Cl, Br, 0 < a ≤ 4, 0 < b ≤ 2, 1 ≤ c ≤ 3, 0 ≤ x ≤ 2), and one or more of them can be included.
[0155] In the present application, the modified compound of each of the above positive electrode active materials can be subjected to doping modification or surface coating modification with respect to the positive electrode active material.
[0156] The positive electrode sheet of the present application does not exclude other additional functional layers other than the positive electrode film layer. For example, in some embodiments, the positive electrode sheet of the present application is further sandwiched between the positive electrode current collector and the positive electrode film layer and includes a conductive primer layer (for example, composed of a conductive agent and a binder) provided on the surface of the positive electrode current collector. In some other embodiments, the positive electrode sheet of the present application further includes a protective layer that covers the surface of the positive electrode film layer. [Electrolyte]
[0157] The present application does not particularly limit the type of the electrolyte, and it can be selected according to actual needs. For example, the electrolyte can be selected from at least one of a solid electrolyte and a liquid electrolyte (i.e., an electrolytic solution).
[0158] In some embodiments, the electrolyte uses an electrolytic solution. The electrolytic solution contains an electrolyte salt and a solvent.
[0159] The type of the electrolyte salt is not specifically limited and can be selected according to actual needs.
[0160] When the secondary battery of the present application is a lithium ion battery, for example, the electrolyte salt may include at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonylimide (LiFSI), lithium bistrifluoromethanesulfonylimide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), lithium bisoxalate borate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium bis(oxalato)difluorophosphanite (LiDFOP), and lithium tetrafluorooxalate phosphate (LiTFOP).
[0161] When the secondary battery of the present application is a sodium ion secondary battery, and particularly when it is a sodium ion secondary battery, the electrolyte salt may include one or more of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bisfluorosulfonylimide (NaFSI), sodium bistrifluoromethanesulfonylimide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalate borate (NaDFOB), sodium bisoxalate borate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobis(oxalato)phosphate (NaDFOP), and sodium tetrafluorooxalate phosphate (NaTFOP).
[0162] The type of the solvent is not particularly limited and can be selected according to actual needs. In some embodiments, by way of example, the solvent may include one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), methylsulfonylmethane (MSM), ethyl methyl sulfone (EMS), and diethyl sulfone (ESE).
[0163] In some embodiments, the electrolyte preferably further includes an additive, for example, the additive may include an anode film-forming additive, may include a cathode film-forming additive, and may further include an additive that can improve a specific performance of the battery, such as an additive that improves the overcharge characteristics of the battery, an additive that improves the high temperature characteristics of the battery, an additive that improves the low temperature output characteristics of the battery, etc. [Separator]
[0164] The secondary battery using an electrolyte or a secondary battery using a solid electrolyte further includes a separator. The separator is disposed between the positive electrode sheet and the negative electrode sheet and serves to isolate the positive electrode sheet. The present application does not particularly limit the type of the separator, and any known porous structure separator having good chemical stability and mechanical stability may be selected.
[0165] In some embodiments, the separator may be made of one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a monolayer film or a multilayer composite film. When the separator is a multilayer composite film, the materials of each layer may be the same or different.
[0166] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet can be wound or laminated to produce an electrode assembly.
[0167] In some embodiments, the secondary battery may include an exterior material, which is used to encapsulate the electrode assembly and the electrolyte.
[0168] In some embodiments, the secondary battery's exterior material may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The secondary battery's exterior material may be a soft pack, such as a pouch-type soft pack, etc. The material of the soft pack may be plastic, such as one or more of polypropylene (PP), polybutylene terephthalate (PBT), polybutylene succinate (PBS), etc.
[0169] The present application does not particularly limit the shape of the secondary battery, which may be cylindrical, rectangular, or any other shape. Figure 1 shows a secondary battery 5 having a rectangular structure as an example.
[0170] In some embodiments, as shown in FIG. 2, the exterior material may include a housing 51 and a cover plate 53. The housing 51 includes a bottom plate and a side plate connected to the bottom plate. A receiving cavity is formed by being surrounded by the bottom plate and the side plate. The housing 51 has an opening communicating with the receiving cavity, and the cover plate 53 is used to cover the opening and seal the receiving cavity. The electrode assembly 52 may be formed from a positive electrode sheet, a negative electrode sheet, and a separator through a winding process or a lamination process. The electrode assembly 52 is sealed in the receiving cavity. An electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and may be adjusted as needed.
[0171] The method for manufacturing the secondary battery of the present application is well known. In some embodiments, a secondary battery can be formed by assembling a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte. For example, an electrode assembly can be formed from a positive electrode sheet, a separator, and a negative electrode sheet through a winding process or a lamination process, and the electrode assembly can be placed in an exterior material, dried, and then an electrolyte can be injected, and a secondary battery can be obtained through processes such as vacuum sealing, standing, precharging, and shaping.
[0172] In some embodiments of the present application, the secondary battery according to the present application can be assembled into a battery module, and the number of secondary batteries included in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0173] Fig. 3 is a schematic diagram of an example battery module 4. As shown in Fig. 3, in the battery module 4, a plurality of secondary batteries 5 can be arranged in sequence along the length direction of the battery module 4. Of course, any other arrangement may be used. The plurality of secondary batteries 5 can be fixed by fasteners.
[0174] Preferably, the battery module 4 may further include an outer case having an accommodation space in which the plurality of secondary batteries 5 are accommodated.
[0175] In some embodiments, the above battery modules can be further assembled into a battery pack, and the number of battery modules included in the battery pack can be adjusted according to the application and capacity of the battery pack.
[0176] 4 and 5 are schematic diagrams of an example battery pack 1. As shown in Fig. 4 and Fig. 5, the battery pack 1 may include a battery case and a plurality of battery modules 4 installed in the battery case. The battery case includes an upper housing 2 and a lower housing 3, and the upper housing 2 is used to cover the lower housing 3 and form a sealed space that houses the battery modules 4. The plurality of battery modules 4 may be arranged in the battery case in any manner. power consumption equipment
[0177] An embodiment of the present application further provides a power consuming device including at least one of the secondary battery, battery module, or battery pack of the present application. The secondary battery, battery module, or battery pack may be used as a power source of the power consuming device, or may be used as an energy storage element of the power consuming device. The power consuming device may be, but is not limited to, a mobile device (e.g., a mobile phone, a laptop, etc.), an electric vehicle (e.g., a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), a train, a ship, a satellite, an energy storage system, etc.
[0178] The power consumption device can select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0179] 6 is a schematic diagram of an example power consuming device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be used to meet the high power and high energy density requirements of the power consuming device.
[0180] Other examples of power consuming devices include mobile phones, tablet computers, notebook computers, etc. Such power consuming devices are generally required to be lightweight and thin, and can use secondary batteries as a power source. Working Example
[0181] The following examples more specifically describe the contents disclosed in the present application, but since various modifications and changes made within the scope of the contents disclosed in the present application are obvious to those skilled in the art, these examples are merely illustrative.Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without treatment, and all equipment used in the examples are commercially available. Example 1
[0182] The corn starch used as the carbon source is placed in a tubular furnace, heated to 300°C (first temperature t1) at 5°C / min under a nitrogen gas atmosphere, and then heat-treated at a constant temperature for 18 hours (heat treatment time t1) to obtain a first intermediate product. The nitrogen gas atmosphere is changed to a mixed atmosphere of oxygen and argon gas (volume fraction of oxygen is 30%, volume fraction of argon gas is 70%), and then heated to 300°C (second temperature T2) at 3°C / min, and then heat-treated at a constant temperature for 2 hours (heat treatment time T2) to obtain a second intermediate product. The obtained second intermediate product is crushed until the volume particle size Dv50 is 4μm to 8μm and Dv90 is 8μm to 15μm, and then heated to 1100°C (third temperature T3) at 5°C / min under a nitrogen gas atmosphere, and then heat-treated at a constant temperature for 12 hours (heat treatment time T3) to obtain hard carbon. Example 2-23
[0183] The manufacturing method of the hard carbon was the same as that of Example 1, except that the manufacturing process parameters of the hard carbon were adjusted, as shown in Table 1. Comparative Example 1
[0184] The corn starch used as the carbon source is placed in a tubular furnace, heated to 240°C at 3°C / min under a nitrogen gas atmosphere, and then heat-treated at the same temperature for 36 hours to obtain a first intermediate product. The first intermediate product obtained is pulverized to a volume particle size Dv50 of 4μm to 8μm and Dv90 of 8μm to 15μm, and then heated to 1200°C at 5°C / min under a nitrogen gas atmosphere, and then heat-treated at the same temperature for 12 hours to obtain hard carbon. Comparative Example 2
[0185] The corn starch used as the carbon source is placed in a tubular furnace, heated to 240°C at 3°C / min in an air atmosphere, and then heat-treated at the same temperature for 36 hours to obtain a first intermediate product. The first intermediate product obtained is pulverized to a volume particle size Dv50 of 4μm to 8μm and Dv90 of 8μm to 15μm, and then heated to 1200°C at 5°C / min in a nitrogen gas atmosphere, and then heat-treated at the same temperature for 12 hours to obtain hard carbon. Comparative Example 3
[0186] The manufacturing method of the hard carbon was the same as that of Example 1, except that the manufacturing process parameters of the hard carbon were adjusted, as shown in Table 1. Examination section
[0187] (1) TPD-MS analysis of hard carbon
[0188] TPD-MS analysis was performed on the hard carbons produced in each Example and Comparative Example using an Autochem Model II 2920 gas analyzer from Micromeritics Instruments Corporation, USA, and a Hiden HPR-20 R&D mass spectrometer from Hiden Analytical Ltd., UK. The mass spectrometer was calibrated with H2 (molecular weight (m / z) 2), CO (molecular weight (m / z) 28), and CO2 (molecular weight (m / z) 44) before testing.
[0189] 100 mg of hard carbon sample produced in each Example and Comparative Example was placed in a sample tube, and argon gas was introduced at a flow rate of 10 ml / min to 50 ml / min to perform purging and gas replacement for 30 minutes. Then, while maintaining the flow of argon gas, the heating device was started and the temperature was raised from 50°C to 1050°C at a heating rate of 10°C / min, and the gas generated during the heating process was continuously quantitatively analyzed by a mass spectrometer. The substance with molecular weight (m / z) 2 in the detected released gas was H2, the substance with molecular weight (m / z) 28 was CO, and the substance with molecular weight (m / z) 44 was CO2. After the test, the amount of each gas generated was obtained by time integration of the MS curve obtained by the mass spectrometer, and the obtained amount of gas generated was divided by the sample mass, that is, the amount of gas generated from the hard carbon per unit mass of the present application.
[0190] (2) Specific capacity and initial coulombic efficiency test of hard carbon
[0191] The hard carbon and binder styrene butadiene rubber (SBR), thickener sodium carboxymethylcellulose (CMC-Na), and conductive carbon black prepared in each Example and Comparative Example are thoroughly stirred and mixed in an appropriate amount of solvent deionized water in a mass ratio of 96.2:1.8:1.2:0.8 to form a uniform negative electrode paste. The negative electrode paste is uniformly applied to the surface of the copper foil of the negative electrode current collector, dried in an oven, and then prepared for use. Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and NaPF6 is dissolved in the organic solvent to prepare an electrolyte solution with a concentration of 1 mol / L. Then, a CR2430 button battery is assembled in an argon-protected glove box using a metallic sodium sheet as a counter electrode and a polyethylene (PE) film as a separator.
[0192] At 25°C, the button batteries manufactured in each Example and Comparative Example were first discharged at a constant current of 10 mA / g to 0 V, and the first cycle discharge capacity of the button batteries was recorded. Then, the button batteries were charged at a constant current of 10 mA / g to 2.0 V, and the first cycle charge capacity of the button batteries was recorded.
[0193] Specific capacity of hard carbon (mAh / g) = first cycle charge capacity of button cell / mass of hard carbon.
[0194] Initial coulombic efficiency of hard carbon (%) = first cycle charge capacity of button cell / first cycle discharge capacity of button cell × 100%.
[0195] The test results of Examples 1 to 23 and Comparative Examples 1 to 3 are shown in Table 2.
[0196] From the test results of Examples 1 to 23, it can be seen that the hard carbon has both high capacity and initial coulombic efficiency when the requirements that the amount of CO2 generated is 1.0mmoL / g or less and the amount of CO generated is 2.0mmoL / g or less as detected by TPD-MS when the temperature is raised from 50°C to 1050°C are satisfied. From the test results of Examples 1 to 23, it can be seen that the capacity and initial coulombic efficiency of the hard carbon are further improved when the further requirement that the amount of H2 generated is 1.0mmoL / g or less as detected by TPD-MS when the temperature is raised from 50°C to 1050°C is satisfied.
[0197] FIG. 7 is a scanning electron microscope (SEM) photograph of the hard carbon produced in Example 2. As can be seen from FIG. 7, the hard carbon obtained by the production method of the present application has a regular morphology and a uniform size.
[0198] 8 and 9 are the results of TPD-MS analysis of the hard carbons produced in Example 2 and Comparative Example 1, respectively, in which curve I corresponds to a gas with a molecular weight (m / z) of 44 (i.e., CO2), curve II corresponds to a gas with a molecular weight (m / z) of 28 (i.e., CO), and curve III corresponds to a gas with a molecular weight (m / z) of 2 (i.e., H2).
[0199] As shown in FIG. 8, the hard carbon prepared in Example 2 has suitable CO2, CO and H2 generation. As can be seen from the test results in Table 2, the specific capacity of the hard carbon prepared in Example 2 is 411mAh / g, and the initial Coulombic efficiency is 86.4%. Although the mechanism is not yet clear, the inventors speculate that one possible reason is that the content of oxygen-containing functional groups in the hard carbon structure prepared in Example 2 is suitable, the probability of bonding between the oxygen-containing functional groups and the active ions is small, and the irreversible consumption of the active ions is low. In addition, the suitable content of oxygen-containing functional groups can further ensure that there are suitable defects in the hard carbon structure, and the defects in the part can be used as a conductive channel for the active ions inside the hard carbon, which reduces the proportion of the area in which the active ions cannot be inserted inside the hard carbon, improves the utilization rate of the active ion reaction sites in the hard carbon structure, and is favorable for the active ions to be smoothly inserted into the main structure of the hard carbon material, so that the hard carbon prepared in Example 2 has both high capacity and high initial Coulombic efficiency.
[0200] The hard carbons produced in Comparative Examples 1 to 3 did not satisfy the above range (CO2 generation amount of 1.0 mmoL / g or less, CO generation amount of 2.0 mmoL / g or less) in the amount of CO2 and / or CO generated detected by the TPD-MS test, and therefore the capacity and initial coulombic efficiency of the hard carbons were both poor.
[0201] In Comparative Example 1, corn starch was subjected to a low-temperature heat treatment process in an inert atmosphere, and then directly subjected to a high-temperature carbonization process in an inert atmosphere. As shown in Figure 9, the hard carbon produced in Comparative Example 1 did not satisfy the above ranges for either CO2 or CO generation. As can be seen from the test results in Table 2, the specific capacity of the hard carbon produced in Comparative Example 1 was only 251 mAh / g, and the initial coulombic efficiency was only 77.7%.
[0202] Similarly, in Comparative Example 2, corn starch was subjected to a low-temperature heat treatment process in an air atmosphere and then directly subjected to a high-temperature carbonization process in an inert atmosphere, but the produced hard carbon did not have both a high specific capacity and a high initial coulombic efficiency.
[0203] In Comparative Example 3, corn starch was subjected to a low-temperature heat treatment process in an inert atmosphere, a second low-temperature heat treatment process in an oxygen-containing atmosphere, and a high-temperature carbonization process in an inert atmosphere simultaneously. However, the third temperature T3 was too low, so the large amount of highly active structural defects introduced in the process of producing hard carbon could not be effectively reduced, and the formed graphite crystallites contained a large amount of oxygen-containing functional groups, making it difficult for the hard carbon to have both high specific capacity and high initial Coulombic efficiency.
[0204] The present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment that has substantially the same configuration as the technical idea and exhibits the same effect within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can conceive of are added to the embodiment, and other forms constructed by combining some of the components in the embodiment are also included in the scope of the present application, as long as they do not deviate from the gist of the present application.
[0205] [Table 1]
[0206] [Table 2]
Claims
1. CO detected by temperature programmed desorption mass spectrometry (TPD-MS) when the temperature was increased from 50°C to 1050°C 2 The hard carbon has a generation amount of 0.328 mmoL / g to 1.0 mmoL / g, a detected CO generation amount of 0.637 mmoL / g to 2.0 mmoL / g, and a H 2 generation amount detected by temperature programmed desorption mass spectrometry (TPD-MS) when heated from 50°C to 1050°C of 1.215 mmoL / g or less.
2. CO detected by temperature programmed desorption mass spectrometry (TPD-MS) when the temperature was increased from 50°C to 1050°C 2 The amount generated is 0.4mmol / g to 0.8mmol / g, and / or The hard carbon according to claim 1, wherein the amount of CO generated is 0.8 mmoL / g to 1.4 mmoL / g as detected by temperature programmed desorption mass spectrometry (TPD-MS) when the temperature is increased from 50 ° C. to 1050 ° C.
3. H detected by temperature programmed desorption mass spectrometry (TPD-MS) when the temperature was increased from 50°C to 1050°C 2 The hard carbon according to claim 1 or 2, wherein the amount of carbon generated is 1.0 mmoL / g or less.
4. The hard carbon according to claim 3, wherein the amount of H 2 generated is 0.5 to 1.0 mmol / g as detected by temperature programmed desorption mass spectrometry (TPD-MS) when the temperature is increased from 50° C. to 1,050° C.
5. With respect to the total mass of the hard carbon, The mass percentage of the C element is 95% to 98%; and / or The mass percentage of the element O is less than or equal to 5%; and / or The mass percentage of H element is less than or equal to 0.4%; and / or The mass percentage of N element is less than or equal to 0.4%; and / or The hard carbon according to any one of claims 1 to 4, wherein the sum of the mass percentages of C, O, H, and N elements is 99.0% to 99.8%.
6. In the Raman spectrum, I d / I g is 1.2 to 1.3, and I d is 1350±50cm -1 represents the d-band peak intensity in the Raman shift range of g is 1580±50cm -1 The hard carbon according to any one of claims 1 to 5, wherein the g-band peak intensity is in a Raman shift range of
7. The hard carbon according to any one of claims 1 to 6, wherein in an X-ray diffraction spectrum, the 2θ value corresponding to the 002 peak is between 22° and 24°.
8. The volume particle diameter Dv50 is 2 μm to 15 μm. The volume particle diameter Dv90 is 5 μm to 25 μm. The specific surface area is 5 m 2 / g or less; and The green density at a force of 50,000 N is 0.96 g / cm 3 ~1.05g / cm 3 Condition (4) The tap density is 0.80 g / cm 3 ~0.95g / cm 3 The hard carbon according to any one of claims 1 to 7, which satisfies at least one of the following conditions: and condition (5).
9. Condition (1) that the volume particle diameter Dv50 is 4 μm to 8 μm; The volume particle diameter Dv90 is 8 μm to 15 μm.
9. The hard carbon according to claim 1, which satisfies at least one of the following conditions: and condition (3) that the specific surface area is 0.5 m 2 / g to 5 m 2 / g.
10. A step S10 of providing a carbon source; Step S20 of heat-treating the carbon source in an inert atmosphere at a first temperature T1 for a time t1 to obtain a first intermediate product; Step S30 of heat-treating the obtained first intermediate product at a second temperature T2 for a time t2 in an oxygen-containing atmosphere having an oxygen volume fraction of 25% or more to obtain a second intermediate product; A step S31 of crushing the second intermediate product obtained in the step S30; and a step S40 of carbonizing the obtained second intermediate product in an inert atmosphere at a third temperature T3 for a time t3 to obtain hard carbon. T1≦300° C., T2<400° C., and T3 is 1000° C. to 1600° C., The hard carbon was heated from 50° C. to 1050° C., and the CO 2 The amount of CO generated is 0.328 mmoL / g to 1.0 mmoL / g, the amount of CO generated is detected to be 0.637 mmoL / g to 2.0 mmoL / g, and the amount of H 2 generated is detected by temperature programmed desorption mass spectrometry (TPD-MS) when the temperature is raised from 50°C to 1050°C to be 1.215 mmoL / g or less.
11. The method of claim 10, wherein T1≦T2.
12. T1 is 180°C to 300°C, and / or T2 is between 270°C and 380°C, and / or The method according to claim 10 or 11, wherein T3 is between 1000°C and 1400°C.
13. t1 is between 4h and 60h, and / or t2 is between 1h and 12h, and / or The method according to any one of claims 10 to 12, wherein t3 is between 1h and 12h.
14. The method according to any one of claims 10 to 13, wherein the volume fraction of oxygen in the oxygen-containing atmosphere is between 25% and 100%.
15. The method of claim 14, wherein the volume fraction of oxygen in the oxygen-containing atmosphere is 30% to 80%.
16. The method according to any one of claims 10 to 15, wherein the inert atmosphere is selected from one or more of a nitrogen gas atmosphere, an argon gas atmosphere.
17. After step S20 and before step S30, the method further includes a step (a) of crushing the first intermediate product obtained in step S20, The method according to any one of claims 10 to 16, wherein the second intermediate product has a volume particle size after crushing of Dv50 from 2 μm to 15 μm and / or Dv90 from 5 μm to 25 μm.
18. The method of any one of claims 10 to 17, wherein the carbon source comprises one or more of a polymer, a resin, and a biomass material.
19. The polymer comprises one or more of polyaniline, polypyrrole, and / or The resin comprises one or more of a phenolic resin, an epoxy resin, and / or 20. The method of claim 18, wherein the biomass material comprises one or more of starch, glucose, fructose, maltose, sucrose, cellulose, hemicellulose, lignin, and the starch comprises one or more of cereal starch, potato starch, and legume starch.
20. A secondary battery comprising a negative electrode sheet comprising the hard carbon according to any one of claims 1 to 9.
21. 21. A power consuming device comprising the secondary battery of claim 20.
Citation Information
Patent Citations
Porous carbon
JP2020093977A